Relief of Sitting Pain by Resecting Posterior Femoral Cutaneous Nerve, and Elucidation of Its Anatomical Branching Pattern - Kachniarz, Bartlomiej; Dellon, Arnold Lee (Journal of Reconstructive Microsurgery, 2021)
Background Injury to the posterior femoral cutaneous nerve (PFCN) produces sitting pain in the buttock, posterior thigh, and/or the ischial tuberosity. The anatomy of the PFCN has not been well described, and just one small cohort of patients has been reported to have resection of the PFCN.Methods Retrospective review of all patients undergoing resection of the PFCN for sitting pain by the senior author between 2012 and 2019 was performed. Evaluation was done by chart review, intraoperative description of the anatomy of the PFCN, and the outcome of resection of the PFCN with implantation of the proximal nerve into the gluteus muscle. Outcome was determined by direct patient examination, email reports, and telephonic interview.Results Fifty-two patients were included in this study, of which nine were bilateral operative procedures. Thirty-four patients had sufficient follow-up data at a mean of 23 months (3–85 months, range). MRI evidence of hamstring injury was present in 50% of the patients. The classic PFCN anatomy was present in 44% of limbs with the other 56% having a high division permitting branches to the lateral buttock and posterior thigh to be preserved. In patients with bilateral anatomy observations, symmetry was present in 67%. An excellent result (absence of sitting pain, normal activities of daily living [ADL]) was obtained in 53%, a good result (some residual sitting pain with some reduction in ADL), was obtained in 26% and no improvement was observed in 21% of patients.Conclusion Sitting pain due to injury to the PFCN can be relieved by the resection of the PFCN with implantation of the proximal end into muscle. Presence of an anatomical variation, a high division of the PFCN, can permit preservation of sensation in the lateral buttock and posterior thigh in the patient whose symptoms involve just the perineum and ischial tuberosity.
Keywords: posterior femoral cutaneous nerve; pudendal nerve; sitting pain